Exploring mathematics history: Desargues’ contributions and perspectives of teacher candidates - Putri, Amelia Defrianti; Aziza, Difa; Hiltrimartin, Cecil; Scristia, Scristia; Maharani, Annisa Dwi (Universitas Maritim Raja Ali Haji, 2025)
This research explores the contributions of Girard Desargues, a pivotal but often overlooked mathematician in geometry. The study aims to provide insights, inspire interest, and evaluate the understanding of prospective mathematics teachers regarding Desargues' contributions, particularly his work on projective geometry. Employing a qualitative approach, the research integrates a literature review and a case study. Literature data were sourced from academic journals and books, while the case study involved interviews with students from five mathematics education classes. Open-ended interviews assessed students' familiarity with Desargues and their ability to comprehend and apply his theorem. Data were analyzed through meta-analysis and thematic analysis. The findings categorize student responses into three levels: Medium of Desargues and Desargues Theorem, Intermediate Knowledge of Desargues and Desargues Theorem, and Low of Desargues and Desargues Theorem. The results underscore varying levels of awareness among future mathematics educators and suggest that integrating historical mathematical insights into education may support a deeper understanding of concepts.